2010
DOI: 10.1108/17542411011081392
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in salary in a female‐dominated profession

Abstract: Purpose -The purpose of this paper is to examine the salary and promotion negotiation practices of female and male school psychology practitioners and university instructors of school psychology practitioners in order to determine whether salary differences exist between male and female employees in the field of school psychology, which has become a female-dominated profession. Design/methodology/approach -A total of 191 female and 115 male faculty members and 148 female and 56 male school psychologists comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
9
1
1
Order By: Relevance
“…Research on gender differences in negotiation has long produced mixed results [1]. Although it is generally acknowledged that women are less likely to initiate negotiations (Bowles et al , 2007; Greig, 2008; Small et al , 2007) and to negotiate competitively (Crothers et al , 2010; Walters et al , 1998), findings comparing their economic outcomes have been inconsistent. A meta-analysis by Stuhlmacher and Walters (1999) concluded that women tend to achieve worse economic results than men.…”
Section: Gender Differences In Negotiation: the Effect Of Role Incongruitymentioning
confidence: 99%
“…Research on gender differences in negotiation has long produced mixed results [1]. Although it is generally acknowledged that women are less likely to initiate negotiations (Bowles et al , 2007; Greig, 2008; Small et al , 2007) and to negotiate competitively (Crothers et al , 2010; Walters et al , 1998), findings comparing their economic outcomes have been inconsistent. A meta-analysis by Stuhlmacher and Walters (1999) concluded that women tend to achieve worse economic results than men.…”
Section: Gender Differences In Negotiation: the Effect Of Role Incongruitymentioning
confidence: 99%
“…Therefore, the salary based discrimination increases the chance of job burnout. Respondents of the study believe that earning plays an important role in the longevity of service as their satisfaction with earning has negative associations with job burnout 18. In the later stages of their career, they face more financial pressure to survive with less salary due to increased family demands and a higher rate of inflation.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents of the study believe that earning plays an important role in the longevity of service as their satisfaction with earning has negative associations with job burnout. 18 In the later stages of their career, they face more financial pressure to survive with less salary due to increased family demands and a higher rate of inflation. Therefore, with the passage of time, the financial pressure becomes the key contributor to bad health and job stress for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The debate and research over the gender pay gap and equal remuneration are very rich and multifaceted, yet still topical, as the gender pay gap is a persisting phenomenon across the world (Figueiredo et al , 2015; Aláez-Aller et al , 2011). Recent research on the gender pay gap focuses on several aspects, such as perceptions of the gap (Khoreva, 2011), effects of the national culture (Sidani, 2013; Jamali et al , 2008; Yeganeh and May, 2011) as means of narrowing the gender pay gap and improving the career success of both men and women (Orser and Leck, 2010; Adams et al , 2010; Crothers et al , 2010), each gender’s expectations in terms of pay and success (Davidson et al , 2012), social attitudes (Janssen et al , 2016), antecedents and correlates (Bishu and Alkadry, 2017). Further, the gender pay gap has been studied and documented at different levels of analysis (economy, sector, profession and employer) (Figueiredo et al , 2015; Yanadori et al , 2018) and by scientists from diverse disciplines (political science, sociology, economics, management and legal studies).…”
Section: Introductionmentioning
confidence: 99%